Characterization of Lethal Zygosis Associated with Conjugation in Escherichia coli K-12 - Skurray, Ronald A. (1973)
When F(−) cells are mixed with an excess of Hfr cells there is a lethal event which results in a decrease in the number of F(−) survivors. We have described and discussed the parameters affecting this phenomenon of lethal zygosis, and these include the cultural conditions of both donor and recipient cells prior to mixing and the use of aeration throughout the period of the experiment. The absence of lethal zygosis with filtrates and supernatant fluids from donors suggests a dependence on direct cell-cell contact as found in conjugation. The phenomenon, which is normally observed in liquid media, also occurs on solid media, and use of these two methods has allowed examination of strains of different mating types. Whereas most Hfr strains capable of producing normal yields of recombinants showed killing activity, no F(+) and only one F′ donor produced lethal zygosis. Only F(−) strains were sensitive to this phenomenon. The relationship between lethal zygosis and the various stages of conjugation is discussed.